Experimental investigation on thermal management performance of an integrated heat sink with a piezoelectric micropump. (October 2019) - Tang, Yong; Jia, Mingze; Ding, Xinrui; Li, Zongtao; Wan, Zhenping; Lin, Qinghong; Fu, Ting
Abstract: High integration density is the trend of future electronics. The accompanying heat dissipation remains a serious problem in electronic thermal management. To overcome the high power density of heat dissipation, an integrated heat sink with a piezoelectric micropump (IHS-PMP) was developed. The driving performance of the IHS-PMP, including the output flow rate and pump pressure, was established to investigate the effects of the driving voltage and driving frequency. Additionally, it was found that the working fluid generated bubbles under a thermal load. The inevitable bubbles significantly affected the flow rate of the IHS-PMP. Finally, the effects of the heating power and driving frequency on the thermal management performance of the IHS-PMP were experimentally investigated and analyzed. The results indicated that with the optimal driving parameters of the IHS-PMP and at a heating power of 80 W, the wall temperature rise was 47.3 °C. This indicates that the IHS-PMP had excellent thermal management performance. The IHS-PMP can be regarded as a high-potential component in loop liquid cooling, which is beneficial to the thermal management of electronic devices.